Comprehensive characterization of PD-L1 expression and immunotherapy-related genomic biomarkers in early- versus advanced-stage non-small cell lung cancer - Yujie Chen; Peiyuan Wang; Rong Lian; Mingming Yuan; Pengli Yu; Hao He; Peng Chen; Hang Zhou; Weijie Chen; Derong Zhang; Hui Lin; Shuoyan Liu; et al. (BMC Pulmonary Medicine)
Abstract Background Programmed death-ligand 1 (PD-L1) expression is a key biomarker for predicting the efficacy of immune checkpoint inhibitors (ICIs). With the successful application of perioperative immunotherapy, understanding PD-L1-associated clinical and molecular characteristics in early-stage non-small cell lung cancer (NSCLC) patients is essential. Methods We analyzed 3185 NSCLC patients undergoing targeted next-generation sequencing (NGS) and PD-L1 immunohistochemistry (IHC). Associations between PD-L1 expression and molecular profiles were compared across early- (I-III) and advanced-stage (IV) cohorts. Results In early-stage NSCLC (n = 974), high PD-L1 expression was less common than in advanced-stage patients (lung adenocarcinoma [LUAD]: 7.52% vs. 15.98%, p < 0.001; lung squamous cell carcinoma [LUSC]: 18.33% vs. 20.84%, p = 0.058). For LUAD, high PD-L1 expression was more frequent in older patients, males and smokers. Additionally, LUSC overall showed a higher rate of high PD-L1 expression than LUAD. In LUAD, early-stage patients had a lower proportion of tumor mutation burden-high (TMB-H) compared to advanced-stage patients (p < 0.001), but no significant difference was observed in LUSC (p = 0.597). Early-stage patients also had a lower proportion of immunotherapy resistance genes than advanced-stage (LUAD: 31.15% vs. 48.50%, p = 0.014; LUSC: 13.64% vs. 45.24%, p = 0.0067). Moreover, among LUAD patients with high PD-L1 expression and all LUSC patients, early-stage patients exhibited more significantly different genetic features compared to advanced-stage patients. Conclusions This study provides a comprehensive analysis of immunotherapy-related biomarker rates in early-stage NSCLC patients, offering insights for perioperative immunotherapy research and biomarker analysis. Trial registration Not applicable.